2021
DOI: 10.1002/nag.3287
|View full text |Cite
|
Sign up to set email alerts
|

Insights into ground response during underground coal gasification through thermo‐mechanical modeling

Abstract: This paper presents a coupled thermo-mechanical model to investigate the ground response during underground coal gasification (UCG). The model incorporated the temporal and spatial development of temperature, the gradual growth of the cavity, and temperature-dependent material properties. Model verification was made against two benchmarks to acquire the confidence for the predictive purpose. The first exercise demonstrated the correctness of the model implemented in COMPASS. The second exercise showed that usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Gao et al also conducted thermo-mechanical modeling of the underground coal gasification process to gain insights into the induced ground response, and the effects of cavity size and thermal expansion coefficients of the surrounding rocks were reported. It was found that the maximum deformation of the caprock and base rock were small [26]. Considering the possible risk of groundwater pollution, Otto and Kempka implemented thermo-mechanical simulations of rock behavior in UCG, with an emphasis on the damage-induced permeability enhancement of the surround rocks [27].…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al also conducted thermo-mechanical modeling of the underground coal gasification process to gain insights into the induced ground response, and the effects of cavity size and thermal expansion coefficients of the surrounding rocks were reported. It was found that the maximum deformation of the caprock and base rock were small [26]. Considering the possible risk of groundwater pollution, Otto and Kempka implemented thermo-mechanical simulations of rock behavior in UCG, with an emphasis on the damage-induced permeability enhancement of the surround rocks [27].…”
Section: Introductionmentioning
confidence: 99%